Analysis of thymic generation of shared T‐cell receptor α repertoire associated with recognition of tumor antigens shows no preference for neoantigens over wild‐type antigens - Joonatan Mattila; Silja Sormunen; Nelli Heikkilä; Ilkka P. Mattila; Jari Saramäki; T. Petteri Arstila (Cancer Medicine, 2023)
Abstract Background The number of mutations in cancer cells is an important predictor of a positive response to cancer immunotherapy. It has been suggested that the neoantigens produced by these mutations are more immunogenic than nonmutated tumor antigens, which are likely to be protected by immunological tolerance. However, the mechanisms of tolerance as regards tumor antigens are incompletely understood. Methods Here, we have analyzed the impact of thymic negative selection on shared T‐cell receptor (TCR) repertoire associated with the recognition of either mutated or nonmutated tumor antigens by comparing previously known TCR—antigen—pairs to TCR repertoires of 21 immunologically healthy individuals. Results Our results show that TCRα chains associated with either type of tumor antigens are readily generated in the thymus, at a frequency similar to TCRα chains associated with nonself. In the peripheral repertoire, the relative clone size of nonself‐associated chains is higher than that of the tumor antigens, but importantly, there is no difference between TCRα chains associated with mutated or nonmutated tumor antigens. Conclusion This suggests that the tolerance mechanisms protecting nonmutated tumor antigens are non‐deletional and therefore potentially reversible. As unmutated antigens are, unlike mutations, shared by a large number of patients, they may offer advantages in designing immunological approaches to cancer treatment.